Jabal ash-Sharah, Jordanien. Nabatäische Wohn- und Wirtschaftsstrukturen im Hinterland von Petra. Die Arbeiten der Jahre 2015 und 2016 - Ladurner, Mechthild (e-Forschungsberichte des DAI, 2017)
The landscape of the Jabal ash-Sharah is dissected by agricultural terraces, large clearance mounds, field demarcations and hydraulic barrages, and contains numerous archaeological sites and frequent occurrences of surface material, all bearing witness to the impact of intensive agricultural use on the area over millennia. This new research project studies a part of its settlement history by focusing on farmsteads originating in the 1st century AD. The 2015 survey campaign constitutes a continuation of previous work (eDAI-F 2015/2, 2015, 42–45), documenting a total of 12 ancient farmsteads and their agricultural hinterland, located in the vicinity of Wadi Mousa and at-Tayba.